2016
DOI: 10.1099/jmm.0.000291
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of polar flagella in Klebsiella pneumoniae isolated from a patient with neonatal sepsis

Abstract: The genus Klebsiella belongs to the family Enterobacteriaceae, and is currently considered to be non-motile and non-flagellated. In the present work, 25 Klebsiella strains isolated from nosocomial infections were assessed for motility under different growth conditions. One Klebsiella isolate, KpBUAP021, demonstrated a swim-like motility phenotype. The K. pneumoniae genotype was confirmed by 16S rRNA and rpoB gene sequence analysis. Multilocus sequence typing analysis also revealed that the KpBUAP021 strain pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“… 36 Transmission electron microscopy with Ryu staining also showed that KLP JBUAP021 expresses polar flagella. 41 However, we did not find the involvement of NLRC4 in KLPJ- mediated colitis. Other studies have shown that NLRP3 inflammasomes were involved in regulating colonic immune homeostasis; Huber et al 51 showed that both NLRP3 and NLRP6 inflammasomes mediated production of IL18.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“… 36 Transmission electron microscopy with Ryu staining also showed that KLP JBUAP021 expresses polar flagella. 41 However, we did not find the involvement of NLRC4 in KLPJ- mediated colitis. Other studies have shown that NLRP3 inflammasomes were involved in regulating colonic immune homeostasis; Huber et al 51 showed that both NLRP3 and NLRP6 inflammasomes mediated production of IL18.…”
Section: Discussioncontrasting
confidence: 73%
“…NLRC4 is essential for the KLP -induced production of IL1β, IL17A, and neutrophil chemoattractants in the lungs. 36 Certain strains of KLP have been shown to possess flagella, 41 and flagella can activate NLRC4. 42 However, the data did not show the involvement of NLRC4 in KLPJ- mediated colitis ( Figure 8 B ).…”
Section: Resultsmentioning
confidence: 99%
“…coli , floating biofilm formation has been associated with the presence of curli, flagella, Type 1 pili, siderophores, exopolysaccharide and the sensor kinase QseC [33], and recently, the presence of polar flagella has also been reported in one K . pneumoniae isolate [34]. Despite that, to our knowledge, this is the first time hypervirulent-hypermucoviscous K .…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae is usually a non-flagellated bacterium, although a flagella expressing K . pneumoniae isolate was identified in 2016 [86]. A .…”
Section: Resultsmentioning
confidence: 99%